2005
DOI: 10.1002/glia.20224
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of β1 integrin in microglial chemotaxis and proliferation on fibronectin: Different regulations by ADP through PKA

Abstract: Microglia are immune cells in the brain; their activation, migration, and proliferation have pivotal roles in brain injuries and diseases. Microglia are known to attach firmly to fibronectin, the upregulation of which is associated with several pathological conditions in the CNS, through beta1 integrin and become activated. Extracellular nucleotides can serve as potent signaling molecules. Recently, ATP and ADP were revealed to possess chemoattractive properties to microglia via Gi-coupled P2Y receptors. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 59 publications
7
83
0
Order By: Relevance
“…Some reports stated that the activation of P2Y 12 receptors leads to altered cellular morphology and motility in microglia. ATP/ ADP act on their cognate receptor P2Y 12 , leading to actin aggregation, microglial chemotaxis and process extension [5,6,8,9,44]. In a recent study, it was reported that the phosphorylation of VASP is involved in ADP-induced ruffling and protrusion formation in the BV2 microglial cell line [11].…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
See 3 more Smart Citations
“…Some reports stated that the activation of P2Y 12 receptors leads to altered cellular morphology and motility in microglia. ATP/ ADP act on their cognate receptor P2Y 12 , leading to actin aggregation, microglial chemotaxis and process extension [5,6,8,9,44]. In a recent study, it was reported that the phosphorylation of VASP is involved in ADP-induced ruffling and protrusion formation in the BV2 microglial cell line [11].…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
“…This research also showed that the accumulation of VASP at the phagocytic cup was abolished by inhibition of RhoGTPase. VASP phosphorylation induced by the UDPactivated P2Y 6 receptor may serve as the driving force for the dynamic processes of movement in microglial phagocytosis.…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
See 2 more Smart Citations
“…clopidogrel (also known as Plavix) and ticlopidine [1,[4][5][6], which must be metabolized in vivo prior to receptor inhibition. Recently, the wide distribution of P2Y 12 mRNA in human, mouse, and rat brain tissues was reported [7,8], and the evidence indicates that this receptor is associated with astrocyte function. However, the role of the P2Y 12 receptor in brain function is largely unclear.…”
Section: Introductionmentioning
confidence: 99%